The Glycerate and Phosphorylated Pathways of Serine Synthesis in Plants: The Branches of Plant Glycolysis Linking Carbon and Nitrogen Metabolism - Igamberdiev, Abir U.; Kleczkowski, Leszek A. (Frontiers in Plant Science, 2018)
Serine metabolism in plants has been studied mostly in relation to photorespiration where serine is formed from two molecules of glycine. However, two other pathways of serine formation operate in plants and represent the branches of glycolysis diverging at the level of 3-phosphoglyceric acid. One branch (the glycerate – serine pathway) is initiated in the cytosol and involves glycerate formation from 3-phosphoglycerate, while the other (the phosphorylated serine pathway) operates in plastids and forms phosphohydroxypyruvate as an intermediate. Serine formed in these pathways becomes a precursor of glycine, formate and glycolate accumulating in stress conditions. The pathways can be linked to GABA shunt via transamination reactions and via participation of the same reductase for both glyoxylate and succinic semialdehyde. In this review paper we present a hypothesis of the regulation of redox balance in stressed plant cells via participation of the reactions associated with glycerate and phosphorylated serine pathways. We consider these pathways as important processes linking carbon and nitrogen metabolism and maintaining cellular redox and energy levels in stress conditions.